Proton Gradient Regulation5-Like1-Mediated Cyclic Electron Flow Is Crucial for Acclimation to Anoxia and Complementary to Nonphotochemical Quenching in Stress Adaptation . Issue 4 (19th June 2014) - Kukuczka, Bernadeta; Magneschi, Leonardo; Petroutsos, Dimitris; Steinbeck, Janina; Bald, Till; Powikrowska, Marta; Fufezan, Christian; Finazzi, Giovanni; Hippler, Michael
Abstract : Cyclic electron flow is essential for survival under high light and anoxic conditions. Abstract: To investigate the functional importance of Proton Gradient Regulation5-Like1 (PGRL1) for photosynthetic performances in the moss Physcomitrella patens, we generated a pgrl1 knockout mutant. Functional analysis revealed diminished nonphotochemical quenching (NPQ ) as well as decreased capacity for cyclic electron flow (CEF ) in pgrl1 . Under anoxia, where CEF is induced, quantitative proteomics evidenced severe down-regulation of photosystems but up-regulation of the chloroplast NADH dehydrogenase complex, plastocyanin, and Ca 2+ sensors in the mutant, indicating that the absence of PGRL1 triggered a mechanism compensatory for diminished CEF . On the other hand, proteins required for NPQ, such as light-harvesting complex stress-related protein1 (LHCSR1), violaxanthin de-epoxidase, and PSII subunit S, remained stable. To further investigate the interrelation between CEF and NPQ, we generated a pgrl1 npq4 double mutant in the green alga Chlamydomonas reinhardtii lacking both PGRL1 and LHCSR3 expression. Phenotypic comparative analyses of this double mutant, together with the single knockout strains and with the P. patens pgrl1, demonstrated that PGRL1 is crucial for acclimation to high light and anoxia in both organisms. Moreover, the data generated for the C. reinhardtii double mutant clearly showed a complementary role of PGRL1 and LHCSR3 in managing high light stress response. We conclude that both proteins are needed for photoprotection and for survival under low oxygen, underpinning a tight link between CEF and NPQ in oxygenic photosynthesis. Given the complementarity of the energy-dependent component of NPQ (qE) and PGRL1-mediated CEF, we suggest that PGRL1 is a capacitor linked to the evolution of the PSII subunit S-dependent qE in terrestrial plants.